Coating of vesicles with hydrophilic reactive polymers - Konák, Cestmír; Subr, Vladimír; Kostka, Libor; Stepánek, Petr; Ulbrich, Karel; Schlaad, Helmut (Langmuir, 2008)
Vesicles bearing either cationic (amino) groups or zwitterionic (amino acid) groups on the surface were coated with a reactive multivalent hydrophilic N-(2-hydroxypropyl)methacrylamide polymer (PHPMA) and its positively charged analogue (3 mol % quaternary ammonium groups), both having reactive thiazolidine-2-thione (TT) groups randomly distributed along the polymer chain. The vesicles were dispersed in water at a concentration of 1 mg/mL. The effect of surface charges of model vesicles on the surface coating efficiency was evaluated. The changes in the weight-average molecular weight, in the hydrodynamic size, and in the zeta-potential of model vesicles were tested using light scattering methods. The most effective coating of vesicles was observed for the zwitterionic vesicles coated with the positively charged hydrophilic PHPMA-TT copolymer at a concentration of reactive polymer cp = 2 mg/mL. The coating efficiency was more than 1 order of magnitude higher than that obtained for positively charged vesicles coated by the uncharged hydrophilic polymer at the same cp.
Keywords: Water; molekulová hmotnost; thiazolidiny; Molecular Structure; kationty; molekulární struktura; Cations; Polymethacrylic Acids; Molecular Weight; kyseliny polymethakrylové; voda; Thiazolidines